2008
DOI: 10.1093/alcalc/agn032
|View full text |Cite
|
Sign up to set email alerts
|

Addictions Biology: Haplotype-Based Analysis for 130 Candidate Genes on a Single Array

Abstract: Arrays of haplotype-tagged candidate genes, such as this addictions-focused array, represent a cost-effective approach to generate high-quality SNP genotyping data useful for the haplotype-based analysis of panels of genes such as these 130 genes of interest to alcohol and addictions researchers. The inclusion of the 186 ancestry informative markers allows for the detection and correction for admixture and further enhances the utility of the array.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
281
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(283 citation statements)
references
References 46 publications
1
281
1
Order By: Relevance
“…In our analyses of alcohol consumption, P values for these two SNPs were ≥0.5 in all analyses. We also examined association data within ±50 kb of 121 candidate autosomal genes for addictions (alcoholism, other addictions, and disorders of mood and anxiety) listed in a recent review (14). The SNP with the lowest P value for each of the 121 genes is shown in Table S6.…”
Section: Resultsmentioning
confidence: 99%
“…In our analyses of alcohol consumption, P values for these two SNPs were ≥0.5 in all analyses. We also examined association data within ±50 kb of 121 candidate autosomal genes for addictions (alcoholism, other addictions, and disorders of mood and anxiety) listed in a recent review (14). The SNP with the lowest P value for each of the 121 genes is shown in Table S6.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were also genotyped for 150 ancestry informative markers (Hodgkinson et al, 2008), from which individual ethnic factor scores were computed (Supplementary Materials). The four ethnic factor scores explaining the highest variance (Table 2) were included as covariates in all genetic analyses to control population stratification.…”
Section: Genotypingmentioning
confidence: 99%
“…Ancestry informative markers (AIMs, n ¼ 2500) were extracted from the Illumina array to calculate ancestral proportions for all study participants (missing data for five subjects). Using methods described previously for an AIMs panel including 186 markers (Hodgkinson et al, 2008), which were not available for our data set, the ancestry assessment identified six ethnic factors (Africa, Europe, Asia, Far East Asia, Oceania, and Americas). For subjects who self-reported as Caucasian or white, the mean European factor score was 0.94 (median, 0.96) and the mean African factor score was 0.013 (median, 0.001).…”
Section: Human Association Studymentioning
confidence: 99%